Prosthetic appliance use in the patients with premature shedding of deciduous teeth and its impact on orthodontic treatment: A retrospective study - Qamar, Zeeshan; Shaban, Ibrahim Mohammed; Andejani, Abdullah; Alghamdi, Yazeed; El-Skafi, Hadi; Nema, Aqeil Ahmed; Jafer, Mohammad Jasem; Alkous, Ahmad H. A. Y. (Edelweiss Applied Science and Technology, 2026)
Premature loss of deciduous teeth is a prevalent concern in pediatric dentistry and can disrupt normal occlusal development, often increasing the need for complex orthodontic and prosthodontic interventions. This retrospective observational study assessed the association between early primary tooth loss, malocclusion patterns, and subsequent treatment requirements among children attending dental clinics in Riyadh, Saudi Arabia. Records of 467 patients aged 6–18 years were analyzed. Early loss of deciduous teeth was observed in 39% of patients, most commonly due to dental caries and frequently involving primary molars. Children with premature tooth loss exhibited significantly higher rates of crowding, midline deviation, crossbite, and altered overjet or overbite. These occlusal disturbances often necessitated space management using fixed or removable space maintainers, pediatric partial dentures, or functional appliances to preserve arch length and guide the eruption of permanent successors. Patients with early tooth loss demonstrated a greater need for orthodontic treatment, increased treatment complexity, and prolonged treatment duration. Multivariable analyses identified early deciduous tooth loss as an independent predictor of severe treatment complexity, while timely space maintenance and prosthodontic rehabilitation showed a mitigating effect. These findings emphasize the importance of preserving primary teeth and integrating preventive, orthodontic, and prosthodontic strategies to optimize occlusal development and reduce long-term treatment burden in children.